Implementasi Program Pengabdian Masyarakat: Edukasi Menabung Sejak Dini melalui Sosialisasi dan Pendampingan Belajar bagi Siswa Kelas 5 SDN Antasan Besar 7 Banjarmasin - Ahmad Ridho; Amanda Fauzia Yasmin; Arya Rezky Khaidir; Elisabeth Nathania Angelica Gultom; Fadhila Pasha Rahmadina Putri; Sudirwo Sudirwo; Anna Nur Faidah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aimed to foster financial literacy awareness and develop wise financial behavior from an early age through the “Early Saving Movement” socialization program for fifth-grade students of SDN Antasan Besar 7 Banjarmasin. The activity was conducted face-to-face using an interactive approach that included the delivery of educational materials, group discussions, question-and-answer sessions, simple simulations of money management, and the administration of pre- and post-activity questionnaires to measure changes in students’ knowledge and attitudes. The results of the analysis showed a significant increase in students’ motivation to save by 93% and an improvement in their understanding of the benefits of saving by 58%. These findings indicate that direct socialization methods accompanied by active student engagement are effective in enhancing elementary school students’ financial literacy and interest in simple and practical financial management. However, challenges were still found in controlling students’ consumptive behavior, which is influenced by the family environment and daily social interactions. Therefore, follow-up efforts are needed in the form of regular saving habit programs and the involvement of parents and teachers in supervising students’ financial behavior. Overall, this activity had a positive impact on shaping students’ discipline, responsibility, and financial independence from an early age.